Pelatihan Mindset Change Bagi Guru SMK PSM 2 Takeran Magetan - Surianto, Moh Agung; pahlawan, ilham arifin; Muhamadin, Rilo Chandra (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Teachers are the spearhead of the learning process in educational units. The better the quality of learning implemented by a teacher, the impact it will have on the quality of a school's student graduate output. The current service activity aims to build a mindset change for teachers at the Sabilil Muttaqien Islamic Boarding School (PSM) 2 Vocational School, Magetan Regency, which has the title of Center of Excellence Vocational School. This service activity is carried out in the form of offline training at the Takeran Magetan Highway School location, Magetan Regency. The results of the service show that there is an increase in understanding from vocational school teachers about the importance of changing mindsets in efforts to improve the quality of the learning process in the PSM 2 Takeran Vocational School environment.